An Object Tuple Model for Understanding Pointer and Array in C Language - Rong, Wenge; Xu, Tianfan; Sun, Zhiwei; Sun, Zian; Ouyang, Yuanxin; Xiong, Zhang (IEEE transactions on education, 2023)
Contribution: In this study, an object tuple model has been proposed, and a quasi-experimental study on its usage in an introductory programming language course has been reported. This work can be adopted by all C language teachers and students in learning pointer and array-related concepts. Background: C language has been extensively employed in numerous universities as an introductory programming practice. However, the pointer and array have long been recognized as some of the most difficult concepts for novice students learning C language. To help students become familiar with the concept of pointer and array and also their related operations, a comprehensive understanding from memory management's perspective might be helpful. Research Questions: 1) How does the object tuple model help students understand all kinds of object types from a generalized perspective? 2) Why is it important to let the students consider multiple arrays from a 1-D perspective? and 3) How do the memory-oriented operations from the object's perspective help students comprehensively understand the pointer and array? Methodology: The students were divided into experimental and control groups, and the object tuple model was presented in the experimental group. An examination was conducted at end of the semester, and test data were gathered for further analysis. Findings: The proposed object tuple model is effective in giving students clear guidance and helping them further understand the pointer and array in C language.